Advances of Oxidative Stress Impact in Periodontitis: Biomarkers and Effective Targeting Options - Pouliou, Chrysi; Piperi, Christina (Current Medicinal Chemistry, 2024)
Periodontitis is the most common inflammatory oral disease that affects around 15% of adults and contributes to severe periodontal tissue destruction with subsequent tooth loosening and loss. Among the main pathogenic mechanisms underlying periodontitis, excessive reactive oxygen species production and oxidative stress play a predominant role in inducing both local and systemic damage. Current therapeutic approaches have expanded the conventional methods combined with herbal antioxidant compounds to free radical-scavenging nanomaterials and infrared laser therapy, offering promising pre-clinical evidence in periodontitis management. Herein, we review the pathogenic mechanisms of reactive oxygen species tissue damage, along with recent advances in oxidative stress biomarkers and novel targeting options.
Keywords: periodontitis